Mechanism of Hg(II) immobilization in sediments by sulfate-cement amendment. (April 2016) - Serrano, Susana; Vlassopoulos, Dimitri; O'Day, Peggy A.
Abstract: Reactive amendments such as Portland and super-sulfate cements offer a promising technology for immobilizing metalloid contaminants such as mercury (Hg) in soils and sediments through sequestration in less bioavailable solid forms. Tidal marsh sediments were reacted with dissolved Hg(II) in synthetic seawater and fresh water solutions, treated with Portland cement and FeSO4 amendment, and aged for up to 90 days. Reacted solids were analyzed with bulk sequential extraction methods and characterized by powder X-ray diffraction (XRD), electron microscopy, and synchrotron X-ray absorption spectroscopy at the Hg LIII - and S K-edge. In amended sediments, XRD, SEM and sulfur K-edge XANES indicated formation of gypsum in seawater experiments or ettringite-type (Ca6 Al2 (SO4 )3 (OH)12 . 26H2 O) phases in fresh water experiments, depending on the final solution pH (seawater ∼8.5; freshwater ∼10.5). Analysis of Hg EXAFS spectra showed Cl and Hg ligands in the first- and second-coordination shells at distances characteristic of a polynuclear chloromercury(II) salt, perhaps as a nanoparticulate phase, in both seawater and fresh water experiments. In addition to the chloromercury species, a smaller fraction (∼20–25%) of Hg was bonded to O atoms in fresh water sample spectra, suggesting the presence of a minor sorbed Hg fraction. In the absence of amendment treatment, Hg sorption and resistance to extraction can be accounted for by relatively strong binding by reduced S species present in the marsh sediment detected by S XANES. Thermodynamic calculations predict stable aqueous Hg–Cl species at seawater final pH, but higher final pH in fresh water favors aqueous Hg-hydroxide species. The difference in Hg coordination between aqueous and solid phases suggests that the initial Hg–Cl coordination was stabilized in the cement hydration products and did not re-equilibrate with the bulk solution with aging. Collectively, results suggest physical encapsulation of Hg as a polynuclear chloromercury(II) salt as the primary immobilization mechanism. Graphical abstract: Highlights: Hg(II) sequestration in sediments treated with Portland cement and iron sulfate. Spectroscopic and microscopic characterization elucidates molecular mechanisms. Hg EXAFS shows Cl and Hg characteristic of a polynuclear chloromercury(II) salt. Thermodynamic analysis shows disequilibrium of sorbed Hg with solution after aging. Results suggest physical encapsulation of Hg(II) in stable solid phases.